CircTMEM165 facilitates endothelial repair by modulating mitochondrial fission via miR-192/SCP2 in vitro and in vivo - Yan Liu; Yanyan Yang; Min Li; Xiuxiu Fu; Xiangqin He; Xiaoxin Li; Jae Youl Cho; Pei-feng Li; Tao Yu (iScience, 2024)
Summary: Constitutive explorations indicate a correlation between circular RNAs (circRNAs) and cardiovascular diseases. However, the involvement of circRNAs in endothelial recuperation and in-stent restenosis (ISR) remains underexplored. CircTMEM165 has first been reported to be highly expressed in hypoxic human umbilical vein endothelial cells (HUVECs). Here, we identified that circTMEM165 was downregulated in ISR patients, inversely correlating with ISR severity. Functionally, circTMEM165 was found to be abundant in endothelial cells, inhibiting inflammation, and adhesion. Particularly, we first observed that circTMEM165 could alleviate HUVECs apoptosis and mitochondrial fission induced by lipopolysaccharide (LPS). Mechanistically, circTMEM165, as a miR-192-3p sponge, enhancing SCP2 expression, which serves as a critical regulator of HUVECs biological functions. Moreover, in vivo, circTMEM165 attenuated intimal hyperplasia and facilitated repair following classic rat carotid artery balloon injury model. These findings investigated the circTMEM165-miR-192-3p-SCP2 axis as a critical determinant of endothelial health and a potential biomarker and therapeutic target for vascular disorders.